2014
DOI: 10.1097/ijg.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Surgically Induced Astigmatism Following Glaucoma Surgery in Egyptian Patients

Abstract: Both trabeculectomy and deep sclerectomy induced considerable postoperative astigmatism. A longer follow-up period is recommended to study the different patterns of astigmatism in either procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 3 publications
4
16
0
2
Order By: Relevance
“…[13][14][15] Some authors suggested an ATR, whereas others found a WTR astigmatic shift following filtering surgery. More importantly, this shift appears to be consistently transient.…”
Section: Discussionmentioning
confidence: 97%
“…[13][14][15] Some authors suggested an ATR, whereas others found a WTR astigmatic shift following filtering surgery. More importantly, this shift appears to be consistently transient.…”
Section: Discussionmentioning
confidence: 97%
“…Few reports have compared the SIA among different glaucoma surgeries 7 , 8 or between modified techniques of the same glaucoma surgery. 5 In the current study, the SIA magnitude in the LEC group did not differ markedly from the SIA values obtained from the previously reported vector analysis at 1–6 months after LEC.…”
Section: Discussionmentioning
confidence: 99%
“…Figure shows the trends of post‐operative changes of induced WTR astigmatism based on the combined results of various studies . WTR astigmatism demonstrated a continuous descending trend during a one‐year follow‐up after trabeculectomy, while most of this reduction has occurred during the first month after the surgery.…”
Section: Keratometric Changesmentioning
confidence: 99%